Machining nickel alloys (Nickel Development Institute, 1992)
This publication gives an overview on machining nickel alloys using traditional methods and describes the advances that have been made. A number of very good and useful guides and reference books on the machining of nickel alloys have appeared over the years. They are listed in the References and should be consulted for detailed information on machining conditions. The information in this brochure is based on the experience of producers and users of nickel alloys, and suppliers of cutting tools. This information should be considered only as a starting point in developing a machining program which then may require optimization to suit specific conditions.
Keywords: Nickel alloys.; elektronické knihy; electronic books